ChemInform Abstract: Synthesis and Catalytic Asymmetric Applications of Quinazolinol Ligands. Issue 42 (September 2016) - Karakaya, Idris; Karabuga, Semistan; Mart, Mehmet; Altundas, Ramazan; Ulukanli, Sabri
Abstract: A range of synthesized chiral quinazolinol ligands is investigated for the catalytic activity in both the asymmetric phenylation of aryl aldehydes and the asymmetric epoxidation of chalcones.